Women and migration: gender perspective in the migration policies of the northern triangle of central america - Cano-Blanco, Andrea Jireth; Rocha-Castillo, Alejandra Sofia (Scientific journal of social studies, 2023)
The present study analyzes the inclusion of a gender perspective for the protection of the human rights of migrant women in the migration policies and provisions of the Northern Triangle countries of Central America. This is seen as a necessity arising from the feminization of migration and the gender-based violence experienced by migrant women from the Northern Triangle of Central America. Thus, this work focuses on the systematization and analysis of 19 migration policies and provisions of the Northern Triangle countries. In terms of methodology, a documentary design was selected, based on a descriptive and interpretive paradigm. Among the main findings, it was found that while some migration policies and provisions establish gender as a guiding criterion, most of them rely on the overgeneralization of the issue and gender neutrality. Likewise, although some provisions recognize the vulnerability of female migrants in their principles and objectives, this recognition is not reflected in the strategies for addressing and preventing violence against migrant women. Following this line of thought, it was concluded that there is a lack of gender perspective inclusion in the migration provisions and policies of the Northern Triangle countries of Central America.
Keywords: Gender perspective; women; migration; gender-based violence